Self-Effıcacy, Self-Regulatıon Dan Self-Confıdence Terhadap Kemampuan Pemecahan Masalah Matematika SD - Almuhaimin Sarnav Ituga; Alman (Jurnal Elementaria Edukasia, 2023)
This study adopts a quantitative approach and utilizes an associative causal research design. The research method employed is non-experimental research, using surveys and tests. The aim of this study is to analyze the effects of self-efficacy, self-regulation, and self-confidence on the mathematical problem-solving ability of fifth-grade students at Inpres 17 Sorong Elementary School. The research population consists of 190 fifth-grade students at Inpres 17 Sorong Elementary School, with a sample size of 70 students from 2 classes, selected through cluster random sampling. Data collection is carried out through questionnaires and tests. The gathered data are analyzed using multiple linear regression analysis. The results indicate a significant combined influence of self-efficacy, self-regulation, and self-confidence on the mathematical problem-solving ability of fifth-grade students. The multiple regression model obtained is represented as Y = -153.71 + 0.521X1 + 0.464X2 + 1.124X3, indicating that self-efficacy, self-regulation, and self-confidence exert an influence on mathematical problem-solving ability.